1992
DOI: 10.1017/s0021859600014209
|View full text |Cite
|
Sign up to set email alerts
|

Not all sheep prefer clover: diet selection revisited

Abstract: S U M M A R YSeveral previous studies have shown that the proportion of clover in sheep diets was greater than the proportion of clover in the mixed species swards being grazed. Various hypotheses have been put forward to explain this observation. One widely held hypothesis is that sheep prefer (actively select) clover to grass. This hypothesis was tested by offering 12 sheep, six that had been recently grazing perennial ryegrass and six that had recently been grazing white clover, the choice between foraging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 49 publications
4
72
0
2
Order By: Relevance
“…This transient change in food palatability caused animal to search for a different food and then to eat a diverse diet. Preferences for the food opposite to the one that animals ate previously has also been found in ewes grazing monocultures of clover or rye-grass (Newman et al, 1992;Parsons et al, 1994) and in heifers fed on hays (Ginane et al, 2002). In these studies, the authors suggested that these preferences could be explained by the desire of animals to balance their diet, or to maintain gut flora diversity by seeking rarity, but also by an attractive effect of novelty, considered as a search for diversity.…”
Section: Short-term Choices: Effect Of Recent Dietary Experiencesmentioning
confidence: 87%
“…This transient change in food palatability caused animal to search for a different food and then to eat a diverse diet. Preferences for the food opposite to the one that animals ate previously has also been found in ewes grazing monocultures of clover or rye-grass (Newman et al, 1992;Parsons et al, 1994) and in heifers fed on hays (Ginane et al, 2002). In these studies, the authors suggested that these preferences could be explained by the desire of animals to balance their diet, or to maintain gut flora diversity by seeking rarity, but also by an attractive effect of novelty, considered as a search for diversity.…”
Section: Short-term Choices: Effect Of Recent Dietary Experiencesmentioning
confidence: 87%
“…This was true for sheep preferring the flavour presented first within a conditioning period over that presented second (Arsenos et al, 2000), for ewes preferring the opposite species (i.e. white clover or ryegrass) to the one they had previously grazed (Newman et al, 1992;Parsons et al, 1994), and for heifers temporarily increasing their preference for the hay that had not been offered during the previous period (Ginane et al, 2002). The authors suggested that the preference for the 'new' hay could be explained by (i) the animal's need to select a balanced diet that best meets its homeostatic requirements or (ii) the animals' search for rarity for functional purposes, such as maintaining gut flora diversity or (iii) an attractive effect of novelty, considered as a search for diversity.…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 95%
“…In the literature, the studies on choices between forages of different quality are relative to only one difference in quality, that is in choice trials between rye-grass and clover [1,21,23] or between vegetative and reproductive swards [6], or when one of the two forages is pelleted [3,18].…”
Section: Introductionmentioning
confidence: 99%